Developing Criteria for Asian Facial Skin Health Status Based on a Non-Invasive Skin Test: The Delphi Process - Li N; Zhao M; Yang X; He Y; Yi F (Dove Medical Press, 2022)
Nan Li,1,2 Mengmeng Zhao,3 Xiaoxiao Yang,3 Yifan He,3 Fan Yi3 1Centre for Health Management and Policy Research, School of Public Health Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2NHC Key Lab of Health Economics and Policy Research (Shandong University), Jinan, People's Republic of China; 3Key Laboratory of Cosmetic, China National Light Industry, Beijing Technology and Business University, Beijing, People's Republic of ChinaCorrespondence: Fan Yi, Beijing Technology and Business University, No. 11/33, Fucheng Road, Haidian District, Beijing, 100048, People's Republic of China, Email fantasyee@btbu.edu.cnObjective: We aimed to develop a set of facial skin health criteria, combined with skin characteristics, and then determine two levels of skin condition and skin problems.Methods: Through a literature study and group discussion, an expert consultation index system was initially formed. The Delphi method was used to conduct two rounds of expert opinion consultation. The index was revised, supplemented and reduced based on the experts' ratings and feedback, and the expert score was calculated. The authority and enthusiasm of the experts and the coordination of the expert opinions finally resulted in a new facial skin Health evaluation index system.Results: The first-level indicators are skin problems and skin condition, the second-level indicators are detailed descriptions, and the third-level indicators are indicators that can be measured by an instrument.Conclusion: The construction of this system can be used to quantitatively evaluate the health status of facial skin with the help of commonly used skin measuring instruments. This scientific and reasonable facial skin health evaluation index system allows people to have an objective and accurate understanding of their own facial skin health and to gradually improve their facial skin health under monitorable conditions.Keywords: facial skin health evaluation, index system, Delphi method